2020
DOI: 10.1002/joc.6465
|View full text |Cite
|
Sign up to set email alerts
|

A novel framework for selecting general circulation models based on the spatial patterns of climate

Abstract: General circulation models (GCMs), used for climate change projections, should be able to simulate both the temporal variability and spatial patterns of the observed climate. However, the selection of GCMs in most previous studies was either based on temporal variability or mean spatial pattern of past climate. In this study, a framework is proposed for the selection of GCMs based on their ability to reproduce the spatial patterns for different climate variables. The Kling‐Gupta efficiency (KGE) was used to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 102 publications
1
46
0
Order By: Relevance
“…However, it is expected that the selected GCM will be able to replicate the mean, spatial variability, and distribution of historical climate (Ahmed et al 2020). It is also suggested that the selection of GCMs based on their performance in simulating both rainfall and temperature as both are equally required for most of the climate change studies (Ahmed et al 2019a;Nashwan and Shahid 2020;Shiru et al 2020) GCM simulations disseminated through different phases of coupled model intercomparison project (CMIP) are vital sources for quantitative climate projection over the twenty-first century (Baker and Huang 2014;Eyring et al 2016). The CMIP phase 3 (CMIP3) GCM simulations (Meehl et al 2007) were used to prepare the fourth assessment report of IPCC (Solomon, S. et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is expected that the selected GCM will be able to replicate the mean, spatial variability, and distribution of historical climate (Ahmed et al 2020). It is also suggested that the selection of GCMs based on their performance in simulating both rainfall and temperature as both are equally required for most of the climate change studies (Ahmed et al 2019a;Nashwan and Shahid 2020;Shiru et al 2020) GCM simulations disseminated through different phases of coupled model intercomparison project (CMIP) are vital sources for quantitative climate projection over the twenty-first century (Baker and Huang 2014;Eyring et al 2016). The CMIP phase 3 (CMIP3) GCM simulations (Meehl et al 2007) were used to prepare the fourth assessment report of IPCC (Solomon, S. et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The values of KGE vary between 1 and −∞, where 1 indicates a perfect agreement. The KGE is a robust metric and is also commonly used as a metric for spatial assessment(Zambrano-Bigiarini et al 2017;Ahmed et al 2019a;Nashwan et al 2019;Nashwan and Shahid 2020)…”
mentioning
confidence: 99%
“…General Circulation Models (GCMs) are numerical models that mimic various physical processes that represent different components of the global climate system such as atmosphere, land surface, oceans and cryosphere (Gouda et al, 2018). The future climate projections enables the policymakers to understand the potential impacts of climate change and to form recommendations and mitigation measures (Nashwan and Shahid, 2019). However, the performance of a climate model was region specific due to the uncertainties attributable to the model structure, parametrization, calibration, and so on (IPCC, 2013; Mcsweeney and Jones, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Nash-Sutcliffe Efficiency (Nash and Sutcliffe, 1970), Kling-Gupta Efficiency (Gupta et al, 2009), Pearson's Correlation Coefficient (r) and Index of Agreement (d, Willmott, 1981) are of the most widely used metrics under this category. Error metrics based on quadratic expressions such as r (Chiew et al, 2009;Raju and Kumar, 2014;Jena et al, 2015;Das et al, 2018;Ruan et al, 2018), MSE (Pierce et al, 2009), NSE (Vaze et al, 2011;Mcmahon et al, 2015;Abbasian et al, 2019), RMSE (Jena et al, 2015;Bokke et al, 2017;Xuan et al, 2017;Das et al, 2018), Normalized RMSE (Maxino et al, 2008;Raju et al, 2017;Khan et al, 2018;Zamani andBerndtsson, 2019), d (Das et al, 2018), KGE (Nashwan and Shahid, 2019; were used in the earlier studies. Many researchers opined that the quadratic form (higher powers of absolute error, >1) are biased to extreme events present in the data and hence emphasizes on the match between event of high magnitude (Krause et al, 2005;Moriasi et al, 2007;Waseem et al, 2008;Tian et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Zambrano-Bigiarini et al 2017;Ahmed et al 2019a;Nashwan et al 2019;Nashwan and Shahid 2020) 3.2 Global Performance Indicator (GPI)GPI(Despotovic et al 2015) combines the effects of individual statistical indicators to provide a single measure. The GPI has been used in many other fields as an effective multicriteria decision analysis (MCDA) tool(Behar et al 2015;Despotovic et al 2015).…”
mentioning
confidence: 99%